La contribución de las reglas de Praga a la promoción de la eficiencia en el arbitraje internacional - Stephens-Chu, Gisèle; Teynier, Camille (Pontificia Universidad Católica del Perú, 2020)
The Prague Rules are intended to provide efficiency and reduce costs in conducting arbitration proceedings. The Rules are based on the position that the practice and procedure of international arbitration is too heavily influenced by the adversarial system found in common law jurisdictions, and that the inquisitorial judicial practices of civil law jurisdictions are more conducive to a “streamlined procedure”. In this paper, the authors first consider whether this predicate is accurate and fair. Are adversarial practices the source of inefficiency in international arbitration, or can the reasons be found elsewhere? Next, they compare certain features of the Prague Rules to the IBA Rules on the Taking of Evidence, and examine how both sets of rules differ in substance. Moreover, they address the criticisms that the Prague Rules may pose yet another case of useless rule-making. In fact, the authors critically assess the consequences of an active role of arbitral tribunals in case management and the appropriateness of a controlled use of documentary production, witness evidence (particularly in oral testimony) and appointment of experts.

Las Reglas de Praga están dedicadas a promover la eficiencia y a reducir los costos que suponen la conducción de los procedimientos arbitrales. Las Reglas se asientan sobre las tesis de que la práctica y el proceso del arbitraje internacional están fuertemente influenciados por el sistema adversarial sobre el que descansan las jurisdicciones del common law, y que las prácticas inquisitoriales de las jurisdicciones del civil law son más oportunas para un “proceso simplificado”.En este artículo, las autoras evalúan primero si esta afirmación es exacta y justa. ¿Las prácticas adversariales son la fuente de la ineficiencia en el arbitraje internacional o podemos encontrar razones en otro lado? A continuación, comparan determinadas disposiciones de las Reglas de Praga con las Reglas de la IBA sobre Práctica de Prueba e indagan cómo se diferencian ambos conjuntos de normas. De otro lado, examinan las críticas que señalan que las Reglas de Praga puedan suponer otro caso de reglamentación estéril. De hecho, se realiza una valoración crítica de las consecuencias del rol activo del tribunal arbitral en el manejo de casos y la pertinencia del uso restringido de la producción de prueba documental, la prueba testifical (especialmente en el testimonio oral) y la designación de peritos.
The Contribution of the Prague Rules to Promoting Efficiency in International Arbitration
Keywords: Reglas de praga; Reglas de la iBA; Prueba; Toma de decisiones; Normas procesales civiles; Debido proceso; https://purl.org/pe-repo/ocde/ford#5.05.01